Electrochemotherapy induces apoptotic death in melanoma metastases: a histologic and immunohistochemical investigation - Bigi L; Galdo G; Cesinaro AM; Vaschieri C; Marconi A; Pincelli C; Fantini F (Dove Medical Press, 2016)
Laura Bigi,1 Giovanna Galdo,2 Anna Maria Cesinaro,3 Cristina Vaschieri,1 Alessandra Marconi,4 Carlo Pincelli,4 Fabrizio Fantini5 1Department of Surgical, Medical, Dental and Morphological Sciences, Dermatologic Clinic University of Modena and Reggio Emilia, Modena, 2Plastic Surgery Unit, IRCCS-CROB, Rionero in Vulture (Pz), 3Department of Pathology, 4Department of Surgical, Medical, Dental and Morphological Sciences, Laboratory of Cutaneous Biology, University of Modena and Reggio Emilia, Modena, 5Dermatology Unit, Azienda Ospedaliera “A. Manzoni”, Lecco, Italy Background: Electrochemotherapy (ECT) is increasingly used in the treatment of primary and secondary skin tumors, but little is known about the pathologic mechanism responsible for tumor cell destruction in humans. Knowledge of detailed mechanism of host response after ECT may improve the treatment efficacy related to patient selection and technique refinements.Aim: The aim of the study was to investigate the histopathology and mechanism of cell death after ECT in cutaneous melanoma metastases. Methods: Skin biopsy specimens were sequentially obtained after ECT of cutaneous melanoma metastases, during a follow-up period of 2 months. Results from histologic evaluation and immunohistochemical characterization of the inflammatory infiltrate (CD3, CD4, CD8, CD56, Granzyme-B) were compared with a panel of apoptosis-related markers.Main outcome measures: Evidence of the mechanism of tumor cell damage, identification of histological and immunohistochemical signs of apoptosis and/or necrosis underlining a possible time course of tumor destruction and inflammatory reaction after ECT.Results: Early signs of epidermal degeneration, an increase of the inflammatory infiltrate, and initial tumor cell morphological changes were already detected 10 min after ECT. The cell damage progression, as demonstrated by histological and immunohistochemical evidence using apoptotic markers (TUNEL and caspase-3 staining), reached a climax 3 days after treatment, to continue until 10 days after. Scarring fibrosis and complete absence of tumor cells were observed in the late biopsy specimens. A rich inflammatory infiltrate with a prevalence of T-cytotoxic CD3/CD8-positive cells was detected 3 h after ECT and was still appreciable 3 months later.Conclusion: This study attempts to define the time course and characteristics of tumor response to ECT. The observations suggest both a direct necrotic cell damage and a rapid activation of apoptotic mechanisms that occur in the early phases of the cutaneous reaction to ECT. A persistent immune response of T-cytotoxic lymphocytes could possibly explain the long-term local tumor control. Keywords: electrochemotherapy, melanoma, metastasis, apoptosis